Mordeduras de animais (selvagens e domésticos) e humanaa - Haddad Junior, Vidal [UNESP]; Campos Neto, Manoel Francisco de; Mendes, Adriana Lúcia [UNESP] (Universidade Federal de Goias, 2013)
Human and animal bites are common events representing a significant percentage of emergency medical care. In addition to acute complications such as bleeding and major lacerations, severe infections may occur for both common and unusual species of bacteria. The treatment involves two steps: first aid measures and long term care, for the treatment of secondary infections and repair of damaged tissues. This review discusses these aspects, considering that the medical and other members of the health care team should be aware of complications and therapeutic approaches proposed for these type of injuries.

As mordeduras humanas e de animais domésticos e selvagens são comuns e representam uma porcentagem importante dos atendimentos médicos de urgência. Além de complicações agudas como sangramento e grandes lacerações, podem ocorrer infecções graves por espécies comuns e incomuns de bactérias. O tratamento envolve duas etapas: as medidas de primeiros socorros e os cuidados tardios para o tratamento das infecções secundárias e reparos de tecidos lesados. Esta atualização discute estes aspectos, levando em consideração que o médico e outros participantes de equipes de saúde devem ter conhecimento destas complicações e das medidas terapêuticas propostas para estes acidentes.
Human and animal bites: an update
Keywords: Bites and stings; Bacterial infections; Antibacterial agents; Wildlife; Domestic animals; Mordeduras e picadas; Infecções bacterianas; Agentes antibacterianos; Animais selvagens; Animais domésticos